Numerical computation and prediction analysis on multilayer flow through porous medium saturated with mono nanofluid - Priyadharshini, P.; Vanitha Archana, M. (Numerical heat transfer. Part A, Applications, 2025)
Many scientific and technological disciplines in the specialization of chemical and petroleum sectors are related to multilayer fluid flow systems. In light of this perspective, the current article focuses on the steady, laminar flow of mono nanofluid saturated with porous media sandwiched between a viscous fluid filled in a vertical channel to develop a new model. The main subject of this scientifical research is to explore the prediction analysis through machine learning algorithm for the physical quantities across the entire region of the proposed fluid. This present physical phenomenon is witnessed in the mathematical form of nonlinear PDEs through the conservation principles and Darcy's law. The system of governing PDEs are nondimensionalized by treating the suitable fundamental variables to facilitate the simulation process. After that, the dimension-free form of momentum and temperature equations is numerically simulated by utilizing the Wolfram language algorithm. In addition, the comparison analysis is accounted to find the higher heat transfer performance for the particles Ag , MgO , and